Time Synchronization and Communication Program of Wireless Sensor Network for Online Monitoring of Electrical Equipment - Shen, Yuxia (International Journal of Online and Biomedical Engineering (iJOE), 2017)
In wireless sensor networks, for improving the time synchronization perfromance of online monitoring and application of ZigBee protocol, a scheme is designed. For this objective, first of all, the ZigBee protocol specification is summarized, a profound analysis of the hardware abstraction architecture of TinyOS operating system is made; the advantages of the ZigBee protocol compared with the traditional radio technology are comparatively analyzed. At the same time, the node design block diagram based on CC2430 and related development system is provided. In the TinyOS2.x operating system, we analyze CC2430 application program abstract architecture, and on this basis, give the realization process of program design. The research results showed that we achieve an on-line monitoring system based on ZigBee protocol, which has realistic significance of applying ZigBee protocol in wireless sensor network of electrical equipment online monitoring. Based on the above research, it is concluded that the online monitoring system can collect the temperature parameters of the monitored object in real time that it can be widely applied in wireless sensor networks.